Effect of surface treatment of T-shaped diatoric holes on the shear bond strength of acrylic artificial teeth with thermoplastic nylon denture base: Study experimental - Melga Syam, Anni'mah Agpabratasino; Wahyuni, Siti (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Surface treatment is a process that modifies the surface of an object that results in changes in morphological structure and physical properties of the material.  Examining the shear bond strength is important to assess the ability to withstand interfacial loads between the artificial tooth surface and the denture base. The purpose of this study was to analyze the effect of surface treatment with T-shaped diatoric holes on the shear bond strength of acrylic artificial teeth with thermoplastic nylon denture base. Methods: This study used 32 samples of maxillary central incisor acrylic artificial teeth bonded with thermoplastic nylon denture bases. The samples were cylindrical with a diameter of 18 mm and a height of 20 mm, divided into four groups: one without surface treatment, and three with surface treatment using T-shaped diatoric holes with diameters of 0.8 mm, 1.2 mm, and 1.8 mm. Shear bond strength was measured using a Universal Testing Machine. The data were analyzed using a One-way Anova test, followed by Least Significant Different (LSD) test. Results: The mean shear bond strength without surface treatment was 0.666 ± 0.151 MPa, while with surface treatment using T-shaped diatoric holes, values were as follows: 0.8 mm was 2.079 ± 0.261 MPa, 1.2 mm was 3.354 ± 0.564 MPa, and 1.8 mm was 4.475 ± 0.639 MPa. The p value was 0.0001 (p < 0.05). Conclusion: There was a difference in the additional effect of surface treatment with T-shaped diatoric holes of 0.8 mm, 1.2 mm, and 1.8 mm on the shear bond strength of acrylic artificial teeth with thermoplastic nylon denture base. The 1.8 mm diameter holes resulted in the highest shear bond strength values.KEY WORDS: surface treatment T-shaped diatoric holes, shear bond strength, thermoplastic nylon basePerbedaan efek penambahan surface treatment T-shaped diatoric holes terhadap kekuatan ikatan geser gigi artifisial akrilik dengan basis gigi tiruan nilon termoplastik: Studi eksperimentalABSTRAKPendahuluan: Surface treatment adalah perlakuan terhadap permukaan suatu benda yang menghasilkan perubahan bentuk morfologi dan perubahan sifat fisis bahan.  Penelitian mengenai kekuatan ikatan geser penting dilakukan untuk melihat kemampuan menahan beban interfacial antara permukaan gigi artifisial dengan basis gigi tiruan. Tujuan penelitian adalah menganalisis perbedaan efek penambahan surface treatment T-shaped diatoric holes terhadap kekuatan ikatan geser gigi artifisial akrilik dengan basis gigi tiruan nilon termoplastik. Metode: Penelitian ini menggunakan 32 sampel gigi artifisial akrilik insisivus sentralis rahang atas yang disatukan dengan basis gigi tiruan nilon termoplastik. Sampel berbentuk silindris dengan diameter 18 mm dan tinggi 20 mm, dibagi menjadi empat kelompok: tanpa surface treatment, dengan surface treatment T-shaped diatoric holes berdiameter 0,8 mm, 1,2 mm, dan 1,8 mm. Pengukuran kekuatan ikatan geser dilakukan menggunakan alat Universal Testing Machine. Hail data dianalisis dengan uji One-way Anova dilanjutkan uji Least Significant Different (LSD). Hasil: Nilai rerata kekuatan ikatan geser tanpa surface treatment adalah 0,666 ± 0,151 MPa, sedangkan dengan surface treatment T-shaped diatoric holes 0,8 mm adalah 2,079 ± 0,261 MPa, 1,2 mm adalah 3,354 ± 0,564 MPa, dan 1,8 mm adalah 4,475 ± 0,639 MPa, dengan nilai p=0,0001 (p<0,05). Simpulan: Terdapat perbedaan efek penambahan antara surface treatment dengan T-shaped diatoric holes 0,8 mm, 1,2 mm, dan 1,8 mm terhadap kekuatan ikatan geser gigi artifisial akrilik dengan basis gigi tiruan nilon termoplastik. Diameter 1,8 mm menghasilkan nilai kekuatan ikatan geser yang lebih besar.KATA KUNCI: surface treatment T-shaped diatoric holes, kekuatan ikatan geser, basis nilon termoplastik.